Power, knowledge, and AI in political decision-making: Review of Coeckelbergh, M. (2022) The Political Philosophy of AI. Cambridge: Polity Press. (186 pages) - Babushkina, Dina (Journal of Human-Technology Relations, 2023)
n/a